Abnormal response of the extremities to pain stimulation immediately after the return of spontaneous circulation from cardiopulmonary arrest. Issue 1 (21st December 2007) - Yanagawa, Y; Sakamoto, T; Okada, Y
Abstract : Objective: A study was undertaken to investigate retrospectively whether or not the appearance of an extensor reaction to pain stimulation immediately after the return of spontaneous circulation (ROSC) from cardiopulmonary arrest (CPA) is a sign of a favourable outcome. Methods: Eighty-six patients, all of whom obtained ROSC and survived more than 1 week, were included in the study. They were divided into three groups: (1) patients with at least one abnormal response of the extremities to pain stimulation within 120 min after CPA (M = 2, 3 group); (2) patients with no motor response to pain stimulation (M = 1 group); and (3) patients with only motor responses >3 on the Glasgow Coma Scale (M = 4–6 group). The following variables were investigated: prehospital setting, neurological findings on arrival, use of induced hypothermic therapy and outcome. The outcome was defined as the best cerebral performance achieved at any time within 1 month of the CPA and classified by analogy with cerebral performance category (CPC) into two groups: (1) good recovery, CPC 1–3; (2) poor recovery, CPC 4–5. Results: The proportion of patients given induced hypothermic therapy in the M = 2, 3 group was greater than in the M = 1 and M = 4–6 groups. Convulsions occurred more frequently in the M = 1 group than in the M = 2, 3 and M = 4–6 groups. The proportion of patients making a good recovery in the M = 1 group (16%; 95% CI 6% to 26%) was smaller than in the M = 2, 3 (81%; 95% CI 68% to 95%) and M = 4–6 groups (88%; 95% CI 72% to 100%). The proportion who survived in each group was similar (M = 1 group: 75% (95% CI 60% to 89%); M = 2, 3 group: 90% (95% CI 81% to 100%); M = 4–6 group: 76% (95% CI 55% to 97%)). In the M = 2, 3 group, four of the five subjects with convulsions did not regain consciousness while 93% (95% CI 83% to 100%) of the subjects in this group without convulsions did regain consciousness. Conclusion: An abnormal response of the extremities to pain stimulation immediately after ROSC tends to be a sign of a favourable outcome in patients without convulsions.